Folder of army intelligence correspondence and memoranda regarding German and IRA activity in Ireland - O'Donoghue, Florence, 1895-1967 (1942)
Includes a handmade Christmas card addressed to O'Donoghue as editor of 'An Cosantóir' and a list of Irishmen employed in Germany and other Irishmen who have come under special notice there.
Keywords: Irish Republican Army; Irish Army. -- Southern Command Supplementary Intelligence Service; Irish Republican Army. -- Southern Command, 1st; World War, 1939-1945 -- Ireland; Ireland -- History -- 1922-